Doing Research Inclusively: Understanding What It Means to Do Research with and Alongside People with Profound Intellectual Disabilities - Catherine de Haas; Joanna Grace; Joanna Hope; Melanie Nind (Social Sciences, 2022)
Positive developments in inclusion in line with ‘Nothing about us without us’ have rarely extended to people with profound intellectual disabilities. Advances in inclusive research are in danger of leaving this group (and their families and allies) on the outside, with researchers relying on proxies at best, or more often omitting this group as ‘too difficult’ to include in the research process at all. This paper argues that finding a way for people with profound intellectual disabilities to belong in inclusive research is important. Using examples, small stories and photographs, it explores and illustrates potential ways to research with and alongside those with profound intellectual disabilities that celebrate different kinds of agency and personhood and that support relational autonomy. The paper concludes that rather than starting from how inclusive research is currently conceived, the starting point should be a deep knowledge of people with profound intellectual and multiple disabilities. The way forward is likely to be an inclusive research culture that can accommodate ‘being with’ as core to its research approach. This will enable the voices of people with profound intellectual disabilities to inform the research in creating intersubjective knowledge together.